Protection of mice against experimental cryptococcosis using glucan particle-based vaccines containing novel recombinant antigens. Issue 3 (16th January 2020) - Hester, Maureen M.; Lee, Chrono K.; Abraham, Ambily; Khoshkenar, Payam; Ostroff, Gary R.; Levitz, Stuart M.; Specht, Charles A.
Highlights: Cryptococcal protein antigens were recombinantly expressed in E. coli . Two mouse strains were vaccinated with recombinant protein-filled glucan particles. After a lethal C. neoformans challenge, vaccine efficacy was assessed by survival. Protection achieved in at least one mouse strain with 11/22 experimental vaccines. Abstract: Meningitis due to Cryptococcus neoformans is responsible for upwards of 180, 000 deaths worldwide annually, mostly in immunocompromised individuals. Currently there are no licensed fungal vaccines, and even with anti-fungal drug treatment, cryptococcal meningitis is often fatal. Our lab previously demonstrated vaccination with recombinant cryptococcal proteins delivered in glucan particles (GPs) protects mice against an otherwise lethal infection. The aim of the present study was to discover additional cryptococcal antigens affording vaccine-mediated protection. Sixteen proteins, each with evidence of extracellularity, were selected for in vivo testing based on their abundance in protective alkaline extracts of an acapsular C. neoformans strain, their known immunogenicity, and/or their high transcript level during human infection. Candidate antigens were recombinantly expressed in E. coli, purified and loaded into GPs. BALB/c and C57BL/6 mice received three subcutaneous injections of GP-based vaccine, and survival was assessed for 84 days following a lethal orotracheal challenge with strain KN99. As with our six published GP-vaccines, we saw differences in overall protection between mouse strains such that BALB/c mice typically demonstrated better survival than C57BL/6 mice. From these studies, we identified seven new proteins which, when administered as GP-vaccines, protect BALB/c and/or C57BL/6 mice against cryptococcal infection. With these results, we expand the pool of novel protective antigens to eleven proteins and demonstrate the potential for selection of highly transcribed extracellular proteins as vaccine targets. These screens highlight the efficacy of GP-subunit vaccines and identify promising antigens for further testing in anti-cryptococcal, multi-epitope vaccine formulations.